Boarding Schools Education and Moral Agents In Kudus Society In Indonesia - Muhamad Zainul Umam (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2021)
This research aims to describe the role of boarding school education as a moral agent in the community in Raudlatul Muta'allimin Jagalan 62 Langgardalem Kudus boarding school. The use of this research in general as a reference to be used as an example of civil society because it has good religious morals. While in particular this research is useful for teachers and students of pondok in order to carry out their duties professionally, full responsibility to improve the quality of learning in boarding schools. The type of research used is qualitative descriptive which is an attempt to provide an overview of situations and events systemistally and factually in boarding schools regarding education in Raudlatul Muta'allimin Jagalan 62 Langgardalem Kudus boarding school. Based on the results of research and data analysis can be concluded that Raudlatul Muta'allimin jagalan 62 Langgardalem Kudus education conducts good learning by blending the surrounding community, so that the community around pesantren has strong Islamic morals. Then in the implementation of learning teachers take action in the management settings of learning in the form of learning mood settings and interaction patterns. Teachers also conduct learning evaluations in the form of written evaluations and practices as well as scripture reading pronability tests